SMARTEST 1st Project Meeting (The Reasoner, 2025)
Report on the the first official meeting of the SMARTEST project which  took place at the CUMO in Noto, Sicily on 9-10 September 2024,
Keywords: SMARTEST; Digital Twins; Machine Learning; Ethics of AI